'Agitate, educate, organise': partisanship, popular music and the Northern Ireland conflict. Issue 2 (May 2020) - Campbell, Sean
Abstract: This article explores popular-musical invocations of the Northern Ireland conflict (1968–1998), focussing specifically on the period between the IRA hunger strike of 1981 and the British Government's Broadcasting Act in 1988. Whilst most songs addressed to the 'Troubles' were marked by (lyrical) abstraction and (political) non-alignment, this period witnessed a series of efforts that issued upfront and partisan views. The article explores two such instances – by That Petrol Emotion and Easterhouse – addressing each band's respective views as well as the specific performance strategies that they deployed in staging their interventions. Drawing on original interviews that the author has conducted with the musicians – alongside extensive archival research of print and audio/visual media – the article explores the bands' songs in conjunction with salient ancillary media (such as record sleeves, videos and interviews), yielding a more nuanced account of popular music's engagement with the 'Troubles' than has been offered in existing work (which often assumes the form of broad surveys).